Methods of studying the cardiovascular system in students of a sports university in the process of recreational rest - Viacheslav Zaytzev; Sergii Iermakov; Karol Gorner; Krzysztof Prusik (Physical Culture, Recreation and Rehabilitation)
Background and Study Aim. The aim of the study is to develop a methodology for examining the cardiovascular system in students with different levels of physical activity.